A Critical Study on Managing Transformation In Indian Banking: Exploring the Impact of Liberalization and Globalization on the Transformation of Indian Banking (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Banksare the most significant players in the Indian financial market because theyare the biggest purveyors of credit and attract most of the savings from thepopulation. Banking plays very important role in the economic development ofall the nations of the world because a developed banking system holds the keyas well as serves as a barometer of economic health of a country. The bankingsector is core competency of the world economy which influences the strength ofevery nation’s economy in the world economy. The overall development and growthof any economy depends more on the sound services sector. The role of servicesector in Indian economic development has increased by several notches from thefact that service sector which was contributing only 20 percent during theindependence time, now it is contributing over 50 pc of GDP India. Indianeconomy is the fastest growing major economy in the world with GDP growth rateof 8.4 percent at the end of third quarter of 2007-08. Hence,Indian banking industry is also growing at the cost of new competitive changesafter liberalization, privatization and globalization. Now, banking sector isperforming well to make every citizen free from poverty, ignorance, financeproblems which had plagued millions of our people for centuries. Further, theperformance of banks is completely linked with the growth of economy andresponse to the requirements of changing environment to make our economy morecompetitive. Because with the globalization trends world over, it is difficultfor any nation, big or small, developed or developing, to remain isolated fromwhat is happening around and such isolation is nearly impossible for Indiaalso. In response to these dynamic changes, India has also adoptedliberalization, privatization and globalization (LPG) policy under bankingsector reforms in 1991 and hence resulted in improved performance andcontinuous developments in every sphere of the banking business. Indian bankingindustry has undergone radical changes due to liberalization and globalizationmeasures and transformation is taking place amid broader changes in bankingsector and the banks are benefiting from increasing globalization of financialservices. Indian banking has succeeded to gain improvement in many aspects ofits business but still information technology is a major challenge to adopt intotality.